EVALUASI CITRA RUMAH SAKIT DI RUMAH SAKIT PKU MUHAMMADIYAH BANTUL - Rifki Albana; Susanto Susanto (Universitas Muhammadiyah Yogyakarta, 2015)
Background: DIY province has 70 hospitals, Bantul district has 10 hospitals that serve 859.968 inhabitants with 793 beds. Although the amount of hospital or beds was not enough, it was important for hospital to keep their image, it’s necessary to maintain or expand their market confidence. Method: It’s Quantitative-Qualitative study, cross-sectional survey and descriptive analytic. The quantitative used for determining images position, It’s used questionnaire to 118 respondents with purposive sampling methode. The qualitative used for supporting quantitative result and became reasons for improvements of dimensional image. Data Analysis used the differential semantic, four instruments and theory of marketing strategic. Result and discussion: There were 23 dimensions of hospital image, all of them show good images, doctors are skilled and experienced (98%.), skilled nursing (92%), professionalism (97%), neat and clean officer’s clothes (92%); organized and comfortable rooms (81%), building and rooms cleanliness (86%); complete facilities (85%), comfortable and hygine facilities (81%); complete medical equipments (88%), complete pharmaceuticals (95%); uncomplicated procedures (93%), officer’s timeliness (76%); sufficient consultation time (83%), attention and sympathy officers (92%), willingness to respond complaints (97%), hospitality (95%); appropriate price (95%), ease of insurance used (88%); strategic location and affordable (97%), inpatient room easily obtained (59%), ease to see the doctor (83%), information access (98%), understandly boards (76%). Image improvement priorities: timeliness officer, ease to see the doctor, adequacy of consultation time, board reconstruction, inpatient room additions, comfortable and hygine facilities, organized and comfortable rooms. Conclusions: All of hospital images were good. There were 7 dimension still need to be improved.